Isolation and Characterization of Friedelin and 5-DodecylResorcinol from the Stem Bark Extract of Pterocarpus erinaceus - Ibrahim, Marwan; Idris, Musa Maikudi; Dauda, Usman; Ali, Umar; Muhammad, Aminu (Journal of Science and Mathematics Letters, 2022)
Pterocarpus erinaceus (Fabaceae) is a medicinal plant used in the treatment of several diseases such as, fever, diarrhea, and dysentery. The aim of this research work is to isolate phytochemicals, evaluate antimicrobial and cytotoxic activities of the extract/isolated compounds from the stem bark of Pterocarpus erinaceus. The plant material was air dried and extracted with a polarity gradient of petroleum ether, ethyl acetate, and methanol. Purification of the methanol extract using column chromatography yielded two compounds: friedelin (1) and 5-dodecylresorcinol (2). Antimicrobial screening of the extracts and isolated compounds was conducted using the disc diffusion method, while the cytotoxicity was tested on the extracts using Brine Shrimp larvae. The methanol extract was more toxic (LC50 of 0.93 µg/mL) than petroleum ether (PER-PE) and ethyl acetate (PER-EA) extracts. Antimicrobial screening of the plant extracts and compounds revealed a moderate activity at 1000 µg/mL.